'Colibacter massiliensis' gen. nov., sp. nov., a new bacterial species isolated from human left colon. (May 2017) - Mailhe, M.; Ricaboni, D.; Vitton, V.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We present here the main characteristics of the strain Marseille-P2911 (= CSUR P2911 = DSMZ 103304), a bacterial species isolated from the left colon liquid sample of a 60-year-old man.